PERSPEKTIF ANTROPOLOGI DALAM SENI DAN ESTETIKA - Simatupang, G.L Lono Asmoro (Acintya, 2010)
This article examine an aesthetic and arts as an anthropological facts related to human being culturally perfected. Originally this article has been presented as a research paper for seminar of aesthetic and arts productivities belonged to marginal ethnic in the Indonesia Institut of Arts in Surakarta, Central Java. Based on a arts productivities and aesthetic production factually this article will strives a relativities of arts product and aesthetic product through the anthropological consepts of culture. There were strong relation according to intercontextual of the termonology of arts itself, the forms and aesthetic products. Here we wont to determined what kind of the definition eventhough therminology had separated from the anthropological perspectives.Â Keyword arts, aesthetic, anthropological perspective